Human Resource Management : A Contemporary Perspective - Beardwell, Ian.; Holden, Len. (London : Pitman, 1997)
This textbook has a strong academic underpinning, easy-to-use features and lecturer support material. The second edition has new chapters on HRM in the public sector and vocational education and training.
Previous ed.: 1994.
Includes bibliographical references and index.
Keywords: Personnel management; Business and Management